2019
DOI: 10.1093/rheumatology/kez243
|View full text |Cite
|
Sign up to set email alerts
|

Fluorodeoxyglucose positron emission tomography/computed tomography in the diagnosis, assessment of disease activity and therapeutic response in relapsing polychondritis

Abstract: Objective To evaluate 18F-fluorodeoxyglucose (FDG) PET/CT in the assessment of disease activity, extent of the disease and response to therapy in relapsing polychondritis. Methods Twenty-five patients (9 men, 16 women) with a mean age of 38.2 years (s.d. 13.7; range 18–62), diagnosed to have relapsing polychondritis according to Damiani and Levine’s modification of McAdam’s criteria, who underwent PET/CT examination were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 30 publications
3
18
1
Order By: Relevance
“…In terms of assessing disease activity, our study showed that both SUV max and PETFBS changed in parallel to the clinical assessment, which was consistent with previous results [11,13,15] . Apart from imaging markers, the nonspeci c serological markers ESR and CRP are routinely used in clinical practice.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In terms of assessing disease activity, our study showed that both SUV max and PETFBS changed in parallel to the clinical assessment, which was consistent with previous results [11,13,15] . Apart from imaging markers, the nonspeci c serological markers ESR and CRP are routinely used in clinical practice.…”
Section: Discussionsupporting
confidence: 91%
“…However, the majority of RP patients with airway involvement were misdiagnosed at their rst visit with a median time of delay to diagnosis of up to more than 10 years [1,4,5] . Our early studies [6][7][8] , along with other previous case reports or sporadic cases have shown that 18F-uorodeoxyglucose positron emission tomography/computed tomography (F-18 FDG PET/CT, hereafter termed PET/CT) with its semiquantitative parameter SUV max may be a helpful tool in aiding in the diagnosis and for therapeutic response monitoring [9][10][11][12][13][14][15] , with typical imaging characteristics of FDG uptake in the laryngo-tracheo-bronchial tree, often symmetrically.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical and symptomatic evaluation, dynamic (inspiratory and expiratory) CT scans and flexible bronchoscopy were critical in establishing the diagnosis of TBM which is consistent with reports from literature [8][9][10]. Other features of RP were identified clinically although recent reports suggest Positron Emission Tomography (PET CT) might be an additional resource for defining the severity and extent of disease [25].…”
Section: Discussionsupporting
confidence: 80%
“…The clinical symptoms improved with the start of oral prednisolone therapy (20 mg/day). In conclusion, FDG‐PET/CT was useful for the differential diagnosis of relapsing polychondritis from asthma 1 …”
Section: Figurementioning
confidence: 93%